2003
DOI: 10.1200/jco.2003.04.112
|View full text |Cite
|
Sign up to set email alerts
|

Fully Synthetic Carbohydrate-Based Vaccines in Biochemically Relapsed Prostate Cancer: Clinical Trial Results With α-N-Acetylgalactosamine-O-Serine/Threonine Conjugate Vaccine

Abstract: A safe synthetic conjugate vaccine in a trimer formation was developed that can break immunologic tolerance by inducing specific humoral responses. It seemed to affect the biochemical progression of the disease as determined by a change in PSA log slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 16 publications
2
110
0
6
Order By: Relevance
“…Synthetic TF and Tn glycoconjugates deserve to be studied from a viewpoint of development of anticancer vaccines [12,13] . Synthetic PAA-glycoconjugates may be promising preparations because they have been described well and can be modified by epitope density or supplemented with the amplifier of immune response and synthesized in necessary quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic TF and Tn glycoconjugates deserve to be studied from a viewpoint of development of anticancer vaccines [12,13] . Synthetic PAA-glycoconjugates may be promising preparations because they have been described well and can be modified by epitope density or supplemented with the amplifier of immune response and synthesized in necessary quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic changes of the level of TFand Tn-antibodies in the serum of patients with cancer and its association with survival have been insufficiently studied. Investigations have mainly focused on clinical trials of antigen-specific immunotherapy [12,13] . The authors have undertaken a long-term follow-up of cancer patients to determine changes in the postoperative level of TFand Tn antibodies, as well as to elucidate the association of this level with the progression of cancer, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines utilizing these Tn, sTn or TF antigens synthesized as trimers or clusters (c) and then conjugated to KLH induced comparable antibody titers by ELISA but far higher and more consistent reactivity against tumor cells. 37,41,42 The improvement in cell surface reactivity resulting from these changes in antigen configuration are summarized in Table 3. Several additional features of these antibody responses should be noted.…”
Section: Modification Of the Tumor Antigen Is Sometimes Requiredmentioning
confidence: 99%
“…For example, mice immunizations with a trimeric cluster of Tn-antigens conjugated to KLH (Tn(c)-KLH) in the presence of the adjuvant QS-21 elicited modest titers of IgG antibodies 28 . In a clinical trial of relapsed prostate cancer patients, the vaccine gave low median IgG and IgM antibody titers 29 . In another study, it was found that only KLH conjugates of glycopeptides composed of multiple repeat units that are highly glycosylated with Tn antigens elicited IgG antibodies 30 .…”
Section: Online)mentioning
confidence: 99%